Studi Tentang Online Public Acces Catalog (OPAC) dalam Peningkatan Kualitas Layanan di Perpustakaan IAIN Metro - Dessy Puspitha (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2021)
This study focuses on of the online public access catalog (OPAC) to improve the quality of library services at the IAIN Metro Library. The type of research used in this research is qualitative research through observation and interviews. With data analysis: First, the use of the OPAC library has not been fully utilized by users effectively and efficiently. Second, the obstacles faced by OPAC are the lack of supporting facilities such as computer software, which are used by OPAC users are not friendly, making it difficult for users to search for information, and the information presented in OPAC is still incomplete. The way to solve problems in using OPAC is to add facilities such as computers, providing guidance or directions to users on how to use OPAC; Libraries must make improvements in the field of information services to provide complete information.